Advancing Gas-cooled Fast Reactor Technology: Outcomes of the Euratom SafeG Project on ALLEGRO Research and Development - Kvizda Boris; Bebjak Slavomír; Mayer Gusztáv; Vácha Petr; Melichar Tomáš; Ding Congjin (EPJ Nuclear Sciences & Technologies)
The paper describes R&D activities suported by Euratom funded projects (SafeG, TREASURE) focused on advancing the development of the Gas-cooled Fast Reactor (GFR) demonstrator ALLEGRO, a key technology in the Generation IV nuclear reactor systems. With the backing of the Generation IV International Forum (GIF) and European Sustainable Nuclear Industrial Initiative (ESNII) of the Sustainable Nuclear Energy Technology Platform (SNETP), GFR technology promises high efficiency in both electricity and industrial heat production, owing to its ability to achieve high core outlet temperatures and close the fuel cycle. The presented activities revolve around addressing crucial technical challenges linked to the ALLEGRO demonstrator. The described projects have brought together leading European and international experts in GFR and High-Temperature Reactor (HTR) technologies. The key outcomes of the SafeG Project include advancements in core safety (WP1), innovative materials (WP2), passive safety systems (WP3), standardization and codes (WP4), and education and training activities (WP5). The future activities are outlined for the follow-up Project TREASURE.